Food Waste and Food Service Satisfaction among Older Adults in Nursing Homes - Farapti, Farapti; Elkarima, Edna; Sari, Dianis Wulan; Winarno, Didik Dwi (Universitas Airlangga, 2023)
Food waste and food service satisfaction can be used of a good food service management. Nursing homes are an institution that also provides food service. This study aims to identify and analyze the association between food waste and food service satisfaction among older adults in the nursing home in Surabaya, Indonesia. A cross-sectional study was conducted on 63 older adults. The 3x24-hour visual Comstock method was used to identify food waste and food service satisfaction was assessed using a questionnaire adapted from the RFSQ (Resident Foodservice Satisfaction Questionnaire) and FoodEx-LTC (Food Expectations-Long-Term Care). Data were analyzed descriptively and inferentially using the Chi-square test. The association between food waste and older adults' food service satisfaction is insignificant (p=0.115). The majority of the older adults (71.4%) were satisfied with the food service and the average of food waste was relatively low (â‰¤20%). However, some menus still had >20% leftovers. It is important to investigate older adults' acceptability and preferences of each menu to minimalize food waste. Menu cycle planning needs to be evaluated periodically and well-designed to meet the nutritional needs of the residents.